Effect of the spreading solvent on the three-phase contact angle of microparticles attached at fluid interfaces - Maestro, Armando (2010)
We address a systematic study of the three-phase contact angle, , of microparticles at flat fluid-liquid interfaces by using different experimental methods. We measured the dependence of not only on the particle chemical composition and size, but also on the solvent used to spread the microparticles onto the fluid interface. We found a non-expected and non-regular dependence of with size, chemical nature and spreading solvent used for the different particles studied. We propose that these dependences are due to porosity/roughness of the particles that allows the adsorption of the spreading solvent onto the solid particle surface. This conclusion is supported by the values of the line tensions estimated for the different systems.